Efficient Damping and Isolation Systems for Civil Structures - Weber, Felix (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Civil engineering structures may vibrate due to different sources of excitations such as earthquakes, wind, traffic, humans, etc. The resulting vibrations may not be acceptable from the perspective of vibration comfort or can even impair the structure's safety. Depending on the excitation mechanism, anti-vibration measures range from increasing the structural damping using local dampers, decoupling the structure from the disturbance using vibration isolators and compensating for the excitation forces using vibration compensators. The Special Issue "Efficient Damping and Isolation Systems for Civil Structures" presents some of the recent advances in the associated fields of research and development.